Match loads of university rugby union players between the 2016 and 2018 Varsity Cup competitions - Gordon, Greg; Morris-Eyton, Heather; Kubayi, Alliance (South African Journal of Sports Medicine, 2020)
Background: Rugby union is a popular and continuously growing sport globally. With the advance of technology, practices have been implemented to quantify the match running demands of rugby union players. The aim of this study was to analyse the match loads of rugby union players between the 2016 and 2018 Varsity Cup competitions. Methods: The sample consisted of 562 match observations of male university rugby union players competing in the Varsity Cup tournaments. Results: The backline players ran significantly longer total distances (5105 m; p = 0.001; ES = 0.49); have greater high- speed running (496 m; p = 0.001; ES = 1.03), very high-speed running (260 m; p = 0.001; ES = 1.50) and sprint distances (117 m; p = 0.001; ES = 1.32) than forward players. Backline players also accumulated a high number of metres per minute (238 ± 94; p = 0.001; ES = 0.46), total Player Load (488 ± 203; p = 0.001; ES = 0.31), RHIE (9 ± 8; p = 0.001; ES = 0.75) and number of accelerations (4 ± 5; p = 0.001; ES = 0.49). Conclusion: These findings may assist coaches to develop player position specific training programmes to meet the physical demands of rugby. Keywords: rugby union, match loads, physical demands, position